A Stochastic Model for Three Species - Suresh Kumar, Y.; Seshagiri Rao, N.; V AppaRao, B. (International Journal of Engineering and Technology, 2018)
The present work is related to a three species ecosystem including a mutualism interaction between two species and a predator, where the predator is depending on both the mutual species. All three species in this model are considered in limited resources. The sustainability of the system (local stability) is discussed through the perturbed technique at the possible existing each equilibrium points. Using Lyapunov's technique the global stability of the system is also described. Further the nature of the system is observed by introducing the stochastic process to the species and the numerical simulations are studied to know the interaction among the species.Â